Praktik Governmentality dan Nativisme dalam Kebijakan Keluarga Berencana Krama Bali - Sukmaning Wahyu, I Putu Rai; Erawan, I Ketut Putra; Jayanthi Mertha, A.A Sagung Mirah Mahaswari (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2020)
ABSTRACT   There is an odd relation between othering practices, efforts to secure native interests, birth control mechanism by introducing ‘four-child norm,’ and  claim to preserve traditional Balinese naming system around the issuance of Krama Bali Family Planning policy. This article aims to explain the relation and  historicity  of  these problems. To  achieve these objectives,  this study uses  two theoretical perspectives: governmentality and nativism. The first perspective serves to investigate specific rationality behind the issuance of Krama Bali Family Planning policy and understand it as a way for the government to manufacture the governable subject; while the second perspective is used to analyze how the governable subjects are formed through  the categorization of natives (orang  ‘asli’ Bali) and  non-natives (pendatang) groups.   Keywords: governmentality, nativism, family planning, krama  Bali